Strategi Kepala Sekolah dalam Mengembangkan Minat dan Bakat Siswa di SMP Muhammadiyah 02 Medan - Rosa Marshanda Harahap; Mesiono Mesiono (LP2M IAIN Sultan Amai Gorontalo, 2024)
This study aims to explain the role of a principal of SMP Muhammadiyah 02 Medan in developing students' interests and talents through various strategic initiatives and programs. Using a descriptive qualitative approach, this study analyzes the principal's profile, the programs implemented, and the positive impacts achieved. The results show that the principal of SMP Muhammadiyah 02 Medan has successfully led the implementation of programs such as improving the quality of teaching, updating school infrastructure, and developing extracurricular activities that improve students' academic achievement. In terms of interests and talents, the principal of SMP Muhammadiyah 02 Medan designed several strategies, namely adding literacy reading materials in the library, providing educational websites and applications as learning resources, providing adequate facilities and infrastructure, good school management, providing opportunities for students to explore interests and talents, and encouraging students' individual motivation and awareness. This strategy will strengthen the character and skills of the students.